2017
DOI: 10.4212/cjhp.v70i2.1641
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Nephrotoxicity Associated with Cisplatin

Abstract: Background: Cisplatin-induced nephrotoxicity occurs in about one-third of patients who receive this chemotherapy drug. In late 2012, the study institution began measuring serum creatinine on day 7 after administration of cisplatin to identify patients with acute renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
(17 reference statements)
0
10
1
Order By: Relevance
“… 1 Almanric et al showed that ACEI/ARBs were used in 29/80 patients (36%), and taking an ACEI or an ARB resulted in an increase of 12.1 µmol/L (95% CI: –15.0, 39.2) in the SCr level, but this increase was found to be statistically insignificant in a multivariate linear and logistic regression analyses. 21 This result was different from our study. This difference may be explained by the possibility that the CIA criteria were different in each study, or that the research population only with stage 4 nonsmall-cell lung cancer or with different tumor types was different.…”
Section: Discussioncontrasting
confidence: 99%
“… 1 Almanric et al showed that ACEI/ARBs were used in 29/80 patients (36%), and taking an ACEI or an ARB resulted in an increase of 12.1 µmol/L (95% CI: –15.0, 39.2) in the SCr level, but this increase was found to be statistically insignificant in a multivariate linear and logistic regression analyses. 21 This result was different from our study. This difference may be explained by the possibility that the CIA criteria were different in each study, or that the research population only with stage 4 nonsmall-cell lung cancer or with different tumor types was different.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in the literature, it is estimated that there is no significant correlation between the number of cures and the onset of nephrotoxicity. 20 Similarly, De Jongh et al 6 reported that the incidence of nephrotoxicity gradually increased with age (OR ¼ 1.03 year À 1; p ¼ 0.007). In the study of Almanric et al, 20 age (p ¼ 0.032) had a statistically significant impact; each year there was an additional increase in serum creatinine; however, gender and dose of cisplatin were not associated with nephrotoxicity, which is consistent with our results gender (p ¼ 0.47), dose of cisplatin (p ¼ 0.089) and age (p ¼ 0.008).…”
Section: Discussionmentioning
confidence: 94%
“…20 Similarly, De Jongh et al 6 reported that the incidence of nephrotoxicity gradually increased with age (OR ¼ 1.03 year À 1; p ¼ 0.007). In the study of Almanric et al, 20 age (p ¼ 0.032) had a statistically significant impact; each year there was an additional increase in serum creatinine; however, gender and dose of cisplatin were not associated with nephrotoxicity, which is consistent with our results gender (p ¼ 0.47), dose of cisplatin (p ¼ 0.089) and age (p ¼ 0.008). On the other hand, Kumaki et al 18 showed no significant association between cisplatin dose (OR ¼ 1.29, p ¼ 0.14) or age (OR ¼ 1, p ¼ 0.87) and nephrotoxicity.…”
Section: Discussionmentioning
confidence: 94%
“…That is why no significant changes in creatinine are observed in case of the patients treated with Manchester RT, revealing a better overall status than the remaining patients. The reason why a decrease in the creatinine levels is not evident in CHRT may be the use of cisplatin-based chemotherapy-this drug is nephrotoxic and tends to increase the creatinine levels [48].…”
Section: Discussionmentioning
confidence: 99%